The Role of Parenting Style and Dietary PUFA and Zinc Intake in Psychomotor Development among Young Children: Binar Panunggal, Gabriela Vania Adhie Ersalina, Diana Nur Afifah, Dewi Marfu’ah Kurniawati, Hartanti Sandi Wijayanti, Mursid Tri Susilo, Lilis Wijayanti, Muti’ah Mustaqimatusy, Rachma Purwanti, Nurmasari Widyastuti, Diana Barsasella, Muhammad Junaid Farrukh - Binar Panunggal; Gabriela Vania Adhie Ersalina; Diana Nur Afifah; Dewi Marfu’ah Kurniawati; Hartanti Sandi Wijayanti; Mursid Tri Susilo; Lilis Wijayanti; Muti’ah Mustaqimatusy; Rachma Purwanti; Nurmasari Widyastuti; Diana Barsasella; Muhammad Junaid Farrukh (Jurnal Persada Husada Indonesia, 2026)
Research Objective: Psychomotor development is an essential component of child growth and development. It can be influenced by several factors, including parenting practices and the adequacy of essential nutrients such as polyunsaturated fatty acids (PUFA) and zinc. This study aimed to examine the relationship between parenting style, PUFA intake, zinc intake, and psychomotor development among toddlers. Methodology: This analytical cross-sectional study involved 66 toddlers aged 7–72 months. Parenting style was assessed using the Parenting Styles and Dimensions Questionnaire (PSDQ). PUFA and zinc intake were measured using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Psychomotor development was evaluated using the Developmental Pre-Screening Questionnaire (KPSP). Data were analyzed using Chi-square tests and ordinal logistic regression. Results: Among the toddlers, 27% were stunted and 26% had mild wasting. Approximately 63% had inadequate PUFA intake, while 68% had inadequate zinc intake. Nearly half of the toddlers (47%) showed questionable psychomotor development. Bivariate analysis showed significant associations between parenting style (p<0.001), PUFA intake (p<0.001), zinc intake (p=0.001), family income (p=0.002), and nutritional status with psychomotor development. Multivariate analysis revealed that zinc intake and family income were the strongest predictors of psychomotor development. Conclusion: Adequate zinc intake and higher family income play important roles in supporting optimal psychomotor development among toddlers. Parenting practices and PUFA intake also contribute to developmental outcomes, although their effects may be mediated by socioeconomic and nutritional factors.